PENGGUNAAN CO BRANDING SEBAGAI UPAYA PERLINDUNGAN HUKUM TERHADAP PRODUK DAERAH - Rahmanu Hidayat; Raden Murjiyanto (Kajian Hukum, 2022)
The purpose of this research is analyzing a system developed by the government of yogyakarta in support of msmb development in the program co-branding yogyakarta, analyze, legal certainty legal protection for all parties in the program co-branding as for the methodology used are juridical empirical research which is that the emphasis on a law which applies, the research was started with research on secondary data which was continued with research on the primary data on the field with the kind of the qualitative study.The results of this research than that to get a license program yogya co-branding msmes should be facing an application and implementation mechanism yogya co-branding program developed by the government in yogyakarta able to provide the impact is economic and legal protection against the landlord government brand yogyakarta special region or umkm as recipients of a license co-branding yogyakarta so that the protection of law inKeywords: law in implementation, village land utilization